ANALISIS PENGARUH ULASAN PRODUK SMARTPHONE TERHADAP NIAT PEMBELIAN: STUDI KASUS CHANNEL GADGETIN DAN JAGAT REVIEW - Yefta Christian; Herman; Eric (JURNAL ILMIAH BETRIK, 2023)
The increase in YouTube users and increasingly popular content creators or what we call influencers has opened up a lot of new potential in product marketing. Smartphone product review content on YouTube is one example of content that can influence consumers' purchasing intentions. This research aims to analyze the influence of smartphone product reviews on YouTube on purchase intentions in Indonesia. The research will be carried out using quantitative methods with case studies on the Gagetin channel and the Jagat Review channel. The data collection method will be carried out by distributing questionnaires in the form of a Google form to 183 respondents for each channel. The collected data was then analyzed using SPSS, Python code, and SEM AMOS. The research results show the same results between the Gadgetin channel and the Jagat Review channel, namely that smartphone product review content on YouTube has a significant influence on consumers' purchasing intentions. The effectiveness of product review content on YouTube will certainly provide new options, especially for new smartphone brand, in promoting their products.